FACTORS INFLUENCING INDONESIAN TOURIST TRAVELLING TO TURKEY DURING THE PANDEMIC - Dina Hariani (Sekolah Tinggi Pariwisata Mataram, 2021)
According to data from the UNWTO, Indonesians made around 11.7 million outbound departures in 2019. The growth in outbound travel in Indonesia was halted by the COVID-19 pandemic, which resulted in global travel restrictions. In June 2020, Turkey has announced a Safe Tourism Certification program, launched to coincide with the start of the 2020 summer season to increase the number of tourists. In July 2020, travel agencies in Indonesia started promoting Turkey tour packages. Since travel agents sold packages to Turkey, the number of Indonesian tourists going to Turkey during the pandemic has increased. This study explores the Turkey Safe Tourism program and factors that influence Indonesian tourists to travel during the pandemic. Using qualitative descriptive methods and for achieving the research objectives the data were collected from secondary sources; researches, journals, articles, and statistical reports. Primary data were collected through interviews and observations of tourists and travel agent guides who already went to Turkey during the pandemic. As the result of this study, Turkey is ready to welcome tourists. Indonesia tourists who came to visit Turkey felt safe because Turkey's conditions are quiet from tourists and health protocols are running well. Travel agencies in Indonesia sell Turkey tour packages because there is demand and purchase. A combination of pent-up wanderlust and lockdown fatigue is driving demand for international travel among Indonesian tourists. Factors that influenced Indonesian tourist travel to Turkey are security, cleanliness priorities, discounted prices, and flexibility.